Mitochondrial impairment induced by chenodeoxycholic acid: The protective effect of taurine and carnosine supplementation - Reza Heidari; Narges Abdoli; Mohammad Mehdi Ommati; Akram Jamshidzadeh; Hossein Niknahad (Shiraz University of Medical Sciences, 2018)
The cholestatic liver disease ensues with a hepatic accumulation of cytotoxic molecules. Several hydrophobic bile acids are known as cytotoxic agents accumulated in the liver during cholestasis. Chenodeoxycholic acid (CDCA) is a toxic hydrophobic bile acid. Oxidative stress and mitochondrial dysfunction are well-known mechanisms of bile acids cytotoxicity. In the current study, CDCA effect on isolated liver mitochondria was monitored by analyzing the changes in mitochondrial dehydrogenases activity, mitochondrial permeabilization, and mitochondrial membrane potential. On the other hand, taurine (1 mM) and carnosine (1 mM) were added as potential protective agents against CDCA-induced mitochondrial dysfunction. Increasing concentrations of CDCA (100 µM - 1000 µM) impaired mitochondrial membrane potential, decreased mitochondrial dehydrogenases activity and enhanced mitochondrial permeabilization and swelling. It was found that taurine and carnosine supplementation preserved mitochondrial function in the presence of CDCA. The results mention that toxicologically relevant concentrations of CDCA impaired mitochondrial function. On the other hand, taurine and carnosine might be applicable as protective agents against bile acids-induced mitochondrial impairment and toxicity.